Fundamentals of sociology - "Gisbert, Pascual" (New Delhi, 2010)
Fundamentals of Sociology is an introduction to the definition, methods and fundamental concepts of sociology. The book prepares the ground for the study of the origins and structures of society and social groups in correlation with other social sciences. In doing so the author looks into the most important facet of social structure social institutions which in their varied forms act as agents of socialization and social control. Dwelling upon key issues in sociology this book details: the questions of social evolution and progress, the role played by heredity, environment and personality, the concerns raised about racial problems, social stratification and the order of culture and civilization, the significant changes that have occurred in economic system and industry, population and food supply, the phenomena that carved out the modern Indian society Green Revolution and industrialization. A comprehensive work, this book has over four decades had a definitive influence on the discipline of sociology. It will continue to be immensely useful for students and teachers.
Keywords: Sociology